The Killed Vessels: Background, Modalities and Possible Meanings in the Prehispanic Cultures of Northwest Argentine. - Moreno, Emanuel Alberto (2024)
In this work we analyze the different modalities and meanings made on the so-called “killed vessels” present in the pre-Hispanic groups of Northwestern Argentina (NOA). To do this, we first start from the study and the meanings given to them throughout the American continent, and then focus on the specific case of the pre-Hispanic Candelaria style.